Relationship of Endothelin-1, Tumor Necrosis Factor-alpha and Interleukin-6 with the Progression of Heart Failure - Mona Yolanda; Marsetio Donosepoetro; Anwar Santoso (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUNDS: Heart failure, a new epidemic of cardiovascular disease, has become an important issue and its prognosis is poor. Heart failure is the condition where the impaired heart cannot pump enough blood to provide the needs of metabolic tissues and organs. Early diagnosis of heart failure is really crucial to determine the success of treatment and to prevent further myocardial dysfunction and worsening clinical symptoms. This condition can be worsened by ET-1, which triggers the secretion of IL-6 and TNF-α as pro inflammation factors. In Systolic Heart Failure, systolic function changes are accompanied by changes in diastolic function. Thus, the condition of systolic heart failure is worse than Diastolic Heart Failure. The purpose of this study is to assess the relationship of ET-1 with diastolic and systolic heart failure groups and the relationship of ET-1 with TNF-α and IL-6 as pro inflammation factors.METHODS: The design of this study was cross-sectional analysis on 62 patients with heart failure, grouped according to the classification of diastolic and systolic heart failure.RESULTS: A significant positive correlation of ET-1 with diastolic and systolic heart failure was found (p=0.008; r=0.324). A significant positive correlation was also found between ET-1 and IL-6 (p=0.001; r=0.393), but a less significant correlation was noted between ET-1 and TNF-α (p=0.201; r=-0.158).CONCLUSIONS: ET-1 has the strongest correlation (p=0.033) with prevalence ratio 3.930 and can differentiate between Diastolic and Systolic Heart Failure.KEYWORDS: Endothelin-1 (ET-1), Interleukin-6 (IL-6), Tumor Necrosis Factor-α (TNF-α), heart failure